2013
DOI: 10.1016/j.neuron.2012.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Corrects Excess Protein Synthesis and Prevents Epileptogenesis in a Mouse Model of Fragile X Syndrome

Abstract: Summary Many neuropsychiatric symptoms of fragile X syndrome (FXS) are believed to be a consequence of altered regulation of protein synthesis at synapses. We discovered that lovastatin, a drug that is widely prescribed for treatment of high cholesterol, can correct excess hippocampal protein synthesis in themouse model of FXS and can prevent one of the robust functional consequences of increased protein synthesis in FXS, epileptogenesis. These data suggest that lovastatin is potentially disease modifying, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
250
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(269 citation statements)
references
References 35 publications
(53 reference statements)
15
250
0
1
Order By: Relevance
“…In addition, animal models provide an opportunity to evaluate novel drug targets to ameliorate FXS symptoms. Indeed, gene therapy (124) and pharmacological compounds such as minocycline (147,201), mGluR5 antagonists (202), arbaclofen (203), ganaxolone (84), lovastatin (204) and lithium (195,205) have shown efficacy in ameliorating some of the phenotypes detected in Fmr1 KO mice. Thorough evaluation of the Fmr1 KO mouse on numerous genetic backgrounds across a multitude of labs indicates that several phenotypes, such as neuronal morphology and hyperactivity, are robust and consistent across studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, animal models provide an opportunity to evaluate novel drug targets to ameliorate FXS symptoms. Indeed, gene therapy (124) and pharmacological compounds such as minocycline (147,201), mGluR5 antagonists (202), arbaclofen (203), ganaxolone (84), lovastatin (204) and lithium (195,205) have shown efficacy in ameliorating some of the phenotypes detected in Fmr1 KO mice. Thorough evaluation of the Fmr1 KO mouse on numerous genetic backgrounds across a multitude of labs indicates that several phenotypes, such as neuronal morphology and hyperactivity, are robust and consistent across studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of FXS, increased density and immature appearance of dendritic spines were detected in patients and mouse models [171,193], and have been widely used to test therapeutic strategies. Pharmacologic and genetic modification of many molecular targets, including neurotransmitter receptors, [62] Lymphoblastoid cells [64], fibroblasts [66] AMPA receptor internalization Increased [43,62,114] N o Altered cellular signaling Increased [64,111,113] or decreased PI3K/mTOR phosphorylation [115]; increased ERK1/2 phosphorylation [112]; increased GSK3ÎČ phosphorylation [116] Lymphoblastoid cells [64], lymphocytes and brain tissue [65], fibroblasts [66] Cellular…”
Section: Synaptic Neuronal and Network Defects To Test Treatment Stmentioning
confidence: 99%
“…Rescue strategies in the FXS mouse model have been based on the analysis of molecular pathomechanisms (e.g., dysregulated mGlu1/5 signaling and protein synthesis), identification of specific FMRP targets that are dysregulated in FXS (e.g., increased protein levels of MMP-9 or striatal-enriched protein tyrosine phosphatase), or have been guided by observations in human patients, and the availability of Food and Drug Administration-approved drugs (N-methyl-D-aspartate antagonists [149]; lovastatin [112]). …”
Section: Therapeutic Targets and Rescue Strategies In The Fxs Mouse Mmentioning
confidence: 99%
“…Many of the proteins upregulated in FXS are believed to be downstream consequences of increased ERK1/2 activity (72), and trials of lovastatin in the Fmr1 KO mouse have shown numerous benefits such as decreasing extracellular receptor kinase-mediated protein synthesis, correcting exaggerated mGluR-mediated LTD, blocking mGluR5-mediated epileptiform bursting hippocampal neurons, dampening hyperexcitability in the visual cortex, and reducing the incidence and severity of seizures (73,74). Recently, a 12-week open label trial of lovastatin in patients with FXS was completed (75); sixteen participants were initially enrolled (mean age = 18 ± 5 years), and 15 subjects finished the study.…”
Section: Lovastatinmentioning
confidence: 99%